Perturbations in the Carotenoid Biosynthesis Pathway in Tomato Fruit Reactivate the Leaf-Specific Phytoene Synthase 2 - Karniel, Uri; Adler Berke, Nastacia; Mann, Varda; Hirschberg, Joseph (Frontiers in Plant Science, 2022)
The accumulation of the red carotenoid pigment lycopene in tomato (Solanum lycopersicum) fruit is achieved by increased carotenoid synthesis during ripening. The first committed step that determines the flux in the carotenoid pathway is the synthesis of phytoene catalyzed by phytoene synthase (PSY). Tomato has three PSY genes that are differentially expressed. PSY1 is exclusively expressed in fruits, while PSY2 mostly functions in green tissues. It has been established that PSY1 is mostly responsible for phytoene synthesis in fruits. Although PSY2 is found in the chromoplasts, it is inactive because loss-of-function mutations in PSY1 in the locus yellow-flesh (r) eliminate carotenoid biosynthesis in the fruit. Here we demonstrate that specific perturbations of carotenoid biosynthesis downstream to phytoene prior and during the transition from chloroplast to chromoplast cause the recovery of phytoene synthesis in yellow-flesh (r) fruits without significant transcriptional changes of PSY1 and PSY2. The recovery of carotenoid biosynthesis was abolished when the expression of PSY2 was silenced, indicating that the perturbations of carotenoid biosynthesis reactivated the chloroplast-specific PSY2 in fruit chromoplasts. Furthermore, it is demonstrated that PSY2 can function in fruit chromoplasts under certain conditions, possibly due to alterations in the plastidial sub-organelle organization that affect its association with the carotenoid biosynthesis metabolon. This finding provides a plausible molecular explanation to the epistasis of the mutation tangerine in the gene CRTISO over yellow-flesh.